Magical realism in contemporary Czech prose - Vaňková, Kristýna (Bohemica Olomucensia, 2025)
Although the term of magical realism has been used since the 1920s, it still seems to be somewhat contradictory and not fully understood. The present study deals, in its introduction, with the nature of the concept of magical realism in the context of literary criticism. Afterwards the study explores the phenomenon of magical realism in contemporary Czech prose, analysing its manifestations in the works of Antonín Bajaja, Anna Cima, Daniela Hodrová, Jáchym Topol, Miroslav Hlaučo, Markéta Pilátová, and Michal Ajvaz - special attention is paid to specific narrative strategies, particularly the blending of temporal planes and the interweaving of reality with fantastical elements because of the author's work with mythology. The study also deals with the issue of Michal Ajvaz's genre affiliation, as his work is often associated with magical realism. This study thus contributes to a deeper understanding of magical realism in Czech literature.
Keywords: magic realism; Czech contemporary prose; literature; literary mode; literary criticism